Representasi Perilaku Nekat Generasi Z Dalam Film Mencuri Raden Saleh: - Fiddaroin, Muhammad Farih; Claretta, Dyva (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Generation Z has many desires and goals that they want to achieve. However, to achieve these goals, Generation Z tends to choose instant methods and does not think long about the risks that will occur. Such reckless behavior from Generation Z has become a picture of reality in today's society. Reckless behavior is shown through the actions taken by generation Z in achieving their goals, which often lead to criminal acts. This research aims to find out how the representation of generation Z's reckless behavior in the film Stealing Raden Saleh. Mencuri Raden Saleh depicts the reality of generation Z's reckless behavior that has resulted in criminality in society. By using John Fiske's semiotic analysis method which divides into three levels of coding (Level of Reality, Level of Representation, and Level of Ideology), it was found that Stealing Raden Saleh represents the reckless behavior of generation Z through criminal acts committed by the six main characters such as forgery, hacking, fighting, and theft. Researchers also found that the reckless behavior of generation Z in the film was also influenced by family background factors and socio-economic conditions.